The vultures, scavenger birds of the Old World and New World - Ospina S., Pedro (2021)
This paper reviews the existing information on the group of birds known as vultures, birds specialized in ingesting carrion, distributed in almost all continents and with similar physical characteristics and behaviors. The objective of the review is to present the global problems and threats to which this group of birds is subjected, mainly due to the anthropic effect, loss of their natural habitat, lead poisoning, and provoked or accidental poisoning, among other factors, that have caused their disappearance in various countries and have placed them on the brink of extinction. The current state of conservation and main threats of the two large groups, vultures of the Old and New World, are reviewed.